Effect of High-dose Vitamin A Supplementation in Children With Sickle Cell Disease: A Randomized, Double-blind, Dose-finding Pilot Study. Issue 2 (March 2020) - Brownell, Jefferson N.; Schall, Joan I.; Mcanlis, Carolyn R.; Smith-Whitley, Kim; Norris, Cynthia F.; Stallings, Virginia A.
Abstract : Suboptimal vitamin A status (serum retinol <30 µg/dL) is associated with poor clinical outcomes in children with the hemoglobin-SS disease (HbSS), and supplementation with the recommended daily allowance of retinol is ineffective in improving vitamin A status. In a single-center randomized blinded dose-finding pilot study, we compared vitamin A and nutritional status in children with HbSS to healthy children and explored the impact of high-dose supplementation on the primary outcome serum vitamin A status. Exploratory outcomes included hematologic, nutritional, immunologic, and muscle function status in children with HbSS. A mixed-effects linear regression model evaluated associations between vitamin A dose, serum retinol, and exploratory outcomes. Twenty healthy children participated, and 22 subjects with HbSS were randomized to oral 3000 or 6000 IU/d retinol for 8 weeks; 21 subjects completed all evaluations. Serum retinol, growth, and nutritional status were all suboptimal in HbSS subjects at baseline, and supplementation did not change vitamin A status. Fetal hemoglobin (Δ=2.5, 95% confidence interval [CI], 0.5-4.3), mean corpuscular volume (Δ=2.7, 95% CI, 0.7-4.7), mean corpuscular hemoglobin (Δ=1.4, 95% CI, 0.5-2.3), and mean corpuscular hemoglobin concentration (Δ=0.5, 95% CI, 0.1-0.9) all improved with supplementation. Mild improvements in erythrocyte indices, growth status, and muscle function occurred independent of hydroxyurea use. Abstract : Supplemental Digital Content is available in the text.